Solve the following system of two equations with two unknowns:

`3+2x-y=0` (1)

`-3-7y=10x` (2)

Write each equation in standard form `(ax+by=c)`.

Subtract 3 to each side of (1).

`2x-y=-3` (3)

Add 3 to each side of (2).

`-7y=10x+3` (2.1)

Subtract 10x to each side of (2.1)

`-10x-7y=3` (4)

Multiply (3) by (5) and add to (4) to solve by elimination.

`10x-5y=-15` (5)

`-10x-7y=3`

---------------------

`-12y=-12` (6)

Divide (6) by -12 to obtain the value of y.

`y=1`

Substitute y=1 in (3)

`2x-1=-3`

Solve for x:

`2x=-3+1`

`x=-2/2=-1`

**Therefore x=-1 and y=1.**

Verify by substituting x=-1 and y=1 in (2)

-3-(7)(1)=10(-1)

-3-7=-10

-10=-10

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now